Asymptomatic Malaria and Associated Risk Factors among School Children in Sanja Town, Northwest Ethiopia. (7th July 2014) - Worku, Ligabaw; Damtie, Demekech; Endris, Mengistu; Getie, Sisay; Aemero, Mulugeta
Abstract : Introduction . Asymptomatic malaria is prevalent in highly endemic areas of Africa and is new challenge for malaria prevention and control strategies. Objective . To determine the prevalence of asymptomatic malaria and associated risk factors among school children in Sanja Town, northwest Ethiopia. Methods. A cross-sectional study was conducted from February to March 2013, on 385 school children selected using stratified proportionate systematic sampling technique. Pretested questionnaire was used to collect sociodemographic data and associated risk factors. Giemsa-stained thin and thick blood films were examined for detection, identification, and quantification of malaria parasites. Data were entered and analyzed using SPSS 20.0 statistical software. Multivariate logistic regression was done for assessing associated risk factors and proportions for categorical variables were compared using chi-square test. P values less than 0.05 were taken as statistically significant. Results . The prevalence of asymptomatic malaria was 6.8% (n = 26 ). The majority of parasitemic study participants had low parasite density 65.5% (17/26). Level of grade, age, bed net usage, and frequent exposure to malaria infection were associated with risk of asymptomatic malaria. Conclusion. Asymptomatic malaria was low in this study area and is associated with level of grade, age, bed net usage, and frequent exposure to malaria infection.